Design of boiler welding for improvement of lifetime and cost control - Atcharawadi Thong-On (2018)
© 2016 by the authors; licensee MDPI, Basel, Switzerland. Fe-2.25Cr-1Mo a widely used material for headers and steam tubes of boilers. Welding of steam tube to header is required for production of boiler. Heat affected zone of the weld can have poor mechanical properties and poor corrosion behavior leading to weld failure. The cost of material used for steam tube and header of boiler should be controlled. This study propose a new materials design for boiler welding to improve the lifetime and cost control, using tungsten inert gas (TIG) welding of Fe-2.25Cr-1Mo tube to carbon steel pipe with chromium-containing filler. The cost of production could be reduced by the use of low cost material such as carbon steel pipe for boiler header. The effect of chromium content on corrosion behavior of the weld was greater than that of the microstructure. The lifetime of the welded boiler can be increased by improvement of mechanical properties and corrosion behavior of the heat affected zone.